Challenges of Work-Life Balance for Women Academics: A Case Study of Universities in Lahore, Pakistan - Bashir, Samra; Khan, Muhammad Ilyas (UMT Education Review, 2022)
To maintain a balance between personal and professional life is important for professionals including academics. Work-life balance helps in achieving and sustaining a healthy work routine that enhances an academic’s effectiveness and satisfaction. In traditional societies, working women often have responsibilities both at their work place and homes. The present study explored that how female academics balance their personal and professional life and what challenges they face in Lahore, Pakistan. The sample consisted of ten female academics selected from two universities in Lahore, Pakistan. Data was collected by using semi-structured interviews and thematic analysis was conducted to analyze the data The findings revealed that women academics faced several problems at their homes as well as their workplace. These problems include lack of departmental support in performing tasks and completing assignments. Also, additional duties are assigned to the women academics, other than their teaching jobs. Women academics were also found to have insufficient time for themselves, leaving an adverse impact on their physical and mental wellbeing. The positive aspect found is that women academics have the courage and potential to cope with these challenges by using different strategies. These strategies include not doing work related tasks at home, sharing problems with family members, and remaining calm and determined.